2022
DOI: 10.1002/lio2.810
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of machine‐delivered sequential massage for the management of lymphedema in the head and neck cancer survivor

Abstract: Background: Lymphedema after treatment for head and neck cancer negatively impacts the quality of life and can produce neck tissue stiffness, dysphagia, pain, and swelling. One form of treatment for lymphedema is machine-delivered sequential lymphedema massage, which is home based and self administered. This study was undertaken to determine economic and system access to home-based lymphedema therapy and to measure patient-reported outcomes among those able to access therapy.Methods: This study is a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…All studies found benefit with APCD use, which was also found to be safe and feasible in 1 RCT and 3 observational studies reporting adverse events. The one RCT compared a 2-month intervention with a waitlist control condition and found improvement in the APCD group in clinician-rated external lymphedema and subjective swallowing, but no improvement in endoscopic assessment of internal lymphedema .…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…All studies found benefit with APCD use, which was also found to be safe and feasible in 1 RCT and 3 observational studies reporting adverse events. The one RCT compared a 2-month intervention with a waitlist control condition and found improvement in the APCD group in clinician-rated external lymphedema and subjective swallowing, but no improvement in endoscopic assessment of internal lymphedema .…”
Section: Resultsmentioning
confidence: 92%
“…Anatomical disease sites were mixed HNC in all studies. Baseline lymphedema severity was not reported in most studies (13 studies). When baseline lymphedema was assessed (4 of 17 studies), all studies reported stages 1b (range, 0-3) on the MDACC-HNL Rating Scale .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations